Step
*
2
of Lemma
subtype-fpf-cap-void2
.....falsecase..... 
1. X : Type
2. eq : EqDecider(X)
3. f : x:X fp-> Type
4. g : x:X fp-> Type
5. x : X
6. z : if x ∈ dom(g) then g(x) else Void fi 
7. ∀x:X. (((↑x ∈ dom(f)) ∧ (↑x ∈ dom(g))) 
⇒ (f(x) = g(x) ∈ Type))
8. ¬↑x ∈ dom(f)
⊢ Void ⊆r if x ∈ dom(g) then g(x) else Void fi 
BY
{ At ⌈Type⌉ (D 0) ⋅ }
1
.....subterm..... T:t
1:n
1. X : Type
2. eq : EqDecider(X)
3. f : x:X fp-> Type
4. g : x:X fp-> Type
5. x : X
6. z : if x ∈ dom(g) then g(x) else Void fi 
7. ∀x:X. (((↑x ∈ dom(f)) ∧ (↑x ∈ dom(g))) 
⇒ (f(x) = g(x) ∈ Type))
8. ¬↑x ∈ dom(f)
9. x1 : Void@i
⊢ x1 ∈ if x ∈ dom(g) then g(x) else Void fi 
2
.....eq aux..... 
1. X : Type
2. eq : EqDecider(X)
3. f : x:X fp-> Type
4. g : x:X fp-> Type
5. x : X
6. z : if x ∈ dom(g) then g(x) else Void fi 
7. ∀x:X. (((↑x ∈ dom(f)) ∧ (↑x ∈ dom(g))) 
⇒ (f(x) = g(x) ∈ Type))
8. ¬↑x ∈ dom(f)
⊢ Void ∈ Type
Latex:
.....falsecase..... 
1.  X  :  Type
2.  eq  :  EqDecider(X)
3.  f  :  x:X  fp->  Type
4.  g  :  x:X  fp->  Type
5.  x  :  X
6.  z  :  if  x  \mmember{}  dom(g)  then  g(x)  else  Void  fi 
7.  \mforall{}x:X.  (((\muparrow{}x  \mmember{}  dom(f))  \mwedge{}  (\muparrow{}x  \mmember{}  dom(g)))  {}\mRightarrow{}  (f(x)  =  g(x)))
8.  \mneg{}\muparrow{}x  \mmember{}  dom(f)
\mvdash{}  Void  \msubseteq{}r  if  x  \mmember{}  dom(g)  then  g(x)  else  Void  fi 
By
At  \mkleeneopen{}Type\mkleeneclose{}  (D  0)  \mcdot{}
Home
Index